On deep level transient spectroscopy of extended defects in n-type 4H-SiC - Weber, Jonas; Weber, Heiko B.; Krieger, Michael (Materials Science Forum, 2017)
We have performed capacitance-voltage (C-V) and deep level transient spectroscopy (DLTS) measurements on Schottky contacts fabricated on triangular defects in 4H-SiC epitaxial layers. These measurements are a case study on the effect of a specific extended defect on the DLTS spectrum in order to contribute to the physical understanding of curious features occasionally observed in DLTS spectra. Our measurements reveal an inversion of the DLTS signal depending on applied voltages and filling pulse lengths, and a step in the C-V characteristic of the Schottky diode. We present a model that qualitatively describes the experimentally obtained data. In this model, we assume that stacking faults within a triangular defect form quantum wells, which can capture electrons from other defects during the DLTS measurement leading to the inversion of the DLTS spectrum. Moreover, by calculating the differential capacitance using a self-consistent Schrödinger- Poisson-Solver, the step in the C-V measurements is reproduced by our model.
CRIS-Team Scopus Importer:2022-04-14
Keywords: DLTS; Extended defects; Quantum well; Stacking faults; Triangular defect